Autocrítica del entendimiento científico-filosófico: autoconocimiento en Spinoza - Cruz Guerrero, Dany Erick (2023)
With Spinoza, modern philosophy reaches a new understanding of subjectivity. Based on the critique of rationalism, Spinoza discovers, for the first time, affectivity for philosophy. The philosopher reflects on the impact of affects on the formation of the ethical subject and thinks that the greatest possible knowledge about one’s own affects results in the collective utility of all of humanity. I maintain that, in the general theory of affects that explains the nature, principles and foundations of affective phenomena, Spinoza nests a timely theory of self-knowledge.